Campylobacter jejuni as a Primary Colonizing Biofilm Former - Hanning, I.; Slavik, M. (International Journal of Poultry Science, 2008)
Campylobacter jejuni can be difficult in the environment and extremely fragile, therefore carry-over between flocks has been difficult to explain. The aim of the study was to determine if the survival of C. jejuni outside the host could be due to a capability to form biofilms. In these experiments, C. jejuni was cultured under conditions of starvation, temperature variations, different cell concentrations, after passage through a chick gastrointestinal tract or with a conditioning film. However, no evidence of attachment and biofilm formation was found outside of growth conditions. Since growth conditions usually do not occur outside the host, it may be concluded that C. jejuni is most likely not a primary biofilm colonizer outside the host. These studies indicate that C. jejuni may utilize a strategy other than primary biofilm formation to survive outside the host.